Reform of the Policy on Public Debt Limits in Fund-Supported Programs-Proposed Decision and Proposed New Guidelines. (Policy Papers; Policy Paper, 2014)
This supplement refers to the reforms proposed in Reform of the Policy on Public Debt Limits in Fund-Supported Programs to the existing framework governing external debt limits in Fund arrangements, and presents the proposed decision that is needed to implement these reforms. The proposed new guidelines are included in the Attachment to the decision, while Annexes I and II set forth for the convenience of Executive Directors include redlined texts that show revisions against the current guidelines and to the Policy Support Instrument decision, respectively.